2017
DOI: 10.1587/elex.14.20161167
|View full text |Cite
|
Sign up to set email alerts
|

kQ-product formula for multiple-transmitter inductive power transfer system

Abstract: This paper formulates the maximum efficiency of multiple-transmitter inductive power transfer system in terms of system kQ-product. We show that the cross-coupling among transmitters does not affect the maximum efficiency. More importantly, the square of system kQ-product is equal to the sum of squares of kQ-products of individual transmitter-receiver links. This result provides an intuitive insight into the characteristics of system efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…11 shows that when the three-coil receive system is located around the transmit coil, even if there is no difference between the receive coils, the energy, output power and transmission efficiency of the system are unevenly distributed to each receive coil due to directional problems. This paper [19] showed that the cross-coupling does not affect the maximum efficiency of multiple-transmitter IPT system. the system efficiency can be simply estimated by measuring the kQ-products of individual transmitter-receiver links.…”
Section: Characteristic Analysis Of Three-coil Transmissionmentioning
confidence: 86%
See 1 more Smart Citation
“…11 shows that when the three-coil receive system is located around the transmit coil, even if there is no difference between the receive coils, the energy, output power and transmission efficiency of the system are unevenly distributed to each receive coil due to directional problems. This paper [19] showed that the cross-coupling does not affect the maximum efficiency of multiple-transmitter IPT system. the system efficiency can be simply estimated by measuring the kQ-products of individual transmitter-receiver links.…”
Section: Characteristic Analysis Of Three-coil Transmissionmentioning
confidence: 86%
“…The frequency conditions for maximum efficiency and power transfer under such couplings are proposed [15,16]. The interesting considerations based on kQ and Q are also given to the magnetic coupled resonance WPT system [17,18,19]. This paper presents a detailed circuit analysis of a two-coil inductively coupled WPT model in different compensating topologies to accomplish efficient energy transfer [20].…”
Section: Introductionmentioning
confidence: 99%
“…An optimization method for output power and transmission efficiency is proposed [15]. The interesting considerations based on kQ and Q are also given to the magnetic coupled resonance WPT system [16,17,18]. In this manuscript, the impedance matching and the maximum power transfer efficiency of a pair of RLC circuits with resonant coupling are analytically derived based on the simplified S-matrix.…”
Section: Introductionmentioning
confidence: 99%
“…These laws fully characterize the relationship between the maximum power transfer efficiency and the port parameter matrix. In recent progress, Duong and Okada presented a theory for power transfer systems to solve a problem involving more than two ports [8]. This was a major step for the possible application deployment of wireless power.…”
Section: Introductionmentioning
confidence: 99%
“…We notice, however, that all those theories seen in Refs. [1,2,3,4,5,6,7,8,9,10] assume reciprocity between the two ports, namely Z 12 ¼ Z 21 . Indeed reciprocity makes the resultant formulas simple and easy to remember, it still confines the versatility of the theory.…”
Section: Introductionmentioning
confidence: 99%